Angiotensin II type 1a-deficient bone marrow-derived dendritic cells produce higher levels of monocyte chemoattractant protein 1 - Nahmod, Karen Amelia (2010)
We read with interest the article from Crowley et al,1 who studied the role of angiotensin II type 1 (AT1) receptors (AT1aR) on immune cells in the pathogenesis of angiotensin II–induced hypertension by generating bone marrow chimeras with wild-type (WT) donors or donors lacking AT1aR. Interestingly, they found that the group of donors lacking AT1aR had more albuminuria and higher expression of a number of inflammatory mediators, including monocyte chemoattractant protein 1 (MCP-1), with persistent infiltration of macrophages in the kidney, concluding that AT1aR on bone marrow–derived cells had protective actions.